Canopy mortality has doubled in Europe’s temperate forests over the last three decades - Cornelius Senf (Nature Portfolio, 2018)
Increases in tree mortality can signal changes in forest health, but large-scale tree mortality is difficult to quantify. Here Senf et al. show large-scale increases in forest mortality in Central Europe over the past 30 years, which were related to increasing growing stocks and temperature.